THE EFFECT OF BRAND IMAGE AND PRODUCT ATTRIBUTES ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY - Indarto, Erik Wahyu; Suroso, Imam; Sudaryanto, Sudaryanto; Qomariah, Nurul (Jurnal Aplikasi Manajemen, 2018)
This study aims to determine the effect of product image and product attributes on customer satisfaction and loyalty of CIMB Niaga Xtra savings at CIMB Niaga Situbondo. The population in this study is the owner of the savings account of CIMB Niaga Xtra until March 2017 with the number of customers reached 152 accounts. Sampling technique used is a non-probability sampling technique that is by accidental sampling. Data analysis method used is Structural Equation Modeling (SEM) analysis. The results showed that product image, product attribute significantly influence customer satisfaction of Bank CIMB Niaga Situbondo. The product image has no significant effect on customer loyalty of Bank CIMB Niaga Situbondo. Product attribute significantly influences customer loyalty of Bank CIMB Niaga Situbondo. Customer satisfaction has a significant effect on customer loyalty of Bank CIMB Niaga Situbondo.